2018
DOI: 10.1111/cts.12537
|View full text |Cite
|
Sign up to set email alerts
|

Physician Awareness of Immune Responses to Polyethylene Glycol‐Drug Conjugates

Abstract: Antibodies against polyethylene glycol (PEG) can critically jeopardize the efficacy and safety of PEGylated therapeutics. For some PEG‐drugs, a sizeable fraction of patients develop anti‐PEG antibodies (APA), leading to reduced efficacy and potential adverse events. We surveyed physicians from several specialties to assess their awareness of APA. Overall, 83% of the physicians surveyed indicated that they have recently prescribed PEGylated drugs. Although 91% of respondents were aware of antidrug antibodies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…We are mindful of the concerns surrounding anti‐PEG immunity, and that its relevance to human patients are still in the infant stage . There is still debate as to why some patients mount a robust immune response to PEG while others do not, and clarification is needed as to why administering PEG‐modified products only sometimes generates clinically observable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We are mindful of the concerns surrounding anti‐PEG immunity, and that its relevance to human patients are still in the infant stage . There is still debate as to why some patients mount a robust immune response to PEG while others do not, and clarification is needed as to why administering PEG‐modified products only sometimes generates clinically observable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it will be important for physicians who regularly prescribe APA-sensitive drugs (such as pegloticase, pegaspargase, and investigational PEGylated compounds) to be aware of the issue of APA. We recently found that only roughly one quarter of physicians who regularly prescribe PEGylated therapeutics are aware that 1) PEG is part of those drugs, and 2) that patients can form antibodies against PEG [53]. Addressing this knowledge gap will be necessary to ensure the continued safe and efficacious use of PEGylated therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…A brief report by McSweeney et al. 54 disclosed that PEG-modified therapeutics can induce specific PEG-binding antibodies, leading to rapid elimination of drugs and a significantly increased risk of serious adverse events.…”
Section: Main Textmentioning
confidence: 99%